EDUKASI PENCEGAHAN BULLYING DI SEKOLAH DASAR PADA SISWA SDN RIDOGALIH 03 - Alivia, Siti; Ekowati, Ekowati; Qintharah, Yuha Nadhirah (An-Nizam, 2024)
This community service was carried out in Ridogalih Village, precisely at SDN Ridogalih 03 against the background of the importance of providing awareness from an early age so that children avoid bullying behavior. In implementing this program, the target of this activity is students. The methods used in this activity are education and interactive dialog. The purpose of this service is to determine the effectiveness of the educational program in reducing bullying cases, increasing awareness, and making schools more positive. The results of this activity show that the educational program has a positive impact, namely increasing student awareness of bullying. This activity can serve as an example for other schools in their efforts to prevent bullying and create a safer and more inclusive learning environment for the next generation. This enables schools to play an active role in protecting students from the negative impact of bullying and improving the overall quality of education.